1993
DOI: 10.1021/j100119a044
|View full text |Cite
|
Sign up to set email alerts
|

Transient small-angle neutron scattering experiments on micellar solutions with a shear-induced structural transition

Abstract: Transient small-angle neutron scattering (SANS) experiments on a sheared 5 mM aqueous surfactant solution of trimethyltetradecylammonium salicylate (TTMA-Sal) are reported. The radially symmetric scattering pattern without shear shows a weak ringlike correlation "peak". For steady shear rates above a threshold value of r t h = 50 s-', the scattering pattern becomes rapidly anisotropic and the ring is compressed into two sharp, symmetric peaks. These changes are related to a shear-induced structural transition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The transition from nonisotropic to isotropic scattering patterns was quantified using the anisotropy parameter A(q), which is defined as the ratio between the scattering intensities in perpendicular and parallel to the flow direction in the detector plane H-V and is given by [31] where I V (q) and I H (q) are the scattering intensities measured in the vertical and in the horizontal axes of the detector plane, in which the scattering vector is perpendicular and Fig. 11.…”
Section: Resultsmentioning
confidence: 99%
“…The transition from nonisotropic to isotropic scattering patterns was quantified using the anisotropy parameter A(q), which is defined as the ratio between the scattering intensities in perpendicular and parallel to the flow direction in the detector plane H-V and is given by [31] where I V (q) and I H (q) are the scattering intensities measured in the vertical and in the horizontal axes of the detector plane, in which the scattering vector is perpendicular and Fig. 11.…”
Section: Resultsmentioning
confidence: 99%
“…6). It was previously reported that cylindrical micelles under shear forces could go through shear-induced alignment [28], with an orientation distribution of the micelles respectively to the flow direction and the incident X-ray beam. The instantaneous angular velocity of the micelles is determined by their orientation relative to the local streamlines [29].…”
Section: Resultsmentioning
confidence: 99%
“…The most important observation that can be made based on the fits is that no change has occurred in the structural parameters of the micelles: the core radius and polydispersity, the micelle length, and the cylinders/sphere ration remained practically constant with increasing shear rate. Following the work of Münch et al [28], we have also calculated the anisotropy parameter A(h), defined as…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1984, SANS has been used to study various aqueous micellar solutions under shear below and slightly above c *. , More recently, time-dependent SANS has been used to study the kinetics of alignment and decay. Studies on two systems containing shear-induced structures (SIS, so-called type II micelles) have found characteristic times on the order of seconds. , …”
Section: Introductionmentioning
confidence: 99%